Examining Village Financial Management through the Lens of Village Officials' Perspective: Case in Penajam Paser Utara - Basri, Basri; Rukaiyah, St.; Sayuti, Nurmadhani Fitri (Jambura Science of Management, 2024)
Purpose: To analyze the extent of management and its implementation in the field of Village financial management in realizing improved services to the community.Design/Methodology/Approach: This type of research is descriptive qualitative. The number of informants in this research was nine people. By using data collection techniques interviews, observation, documentation.Findings: The research findings indicate that village financial management, as perceived by Sidorejo village officials in Penajam sub-district, Penajam Paser Utara district, exhibit well-planned initiatives and effective role fulfillment by all stakeholders. However, challenges persist primarily during the APBDes phase, where delays occur awaiting ADD priority ceiling and regulatory approvals such as PMK DD, and sub-district evaluation results. While implementation progresses smoothly overall, hurdles include slow approval of District APBD impacting village activities, regulatory delays, and uncertain weather conditions affecting project timelines. Additionally, budget discrepancies between field prices and RAB budgets pose challenges. Despite these obstacles, administrative processes function adequately, with active engagement from administrative heads who demonstrate a good understanding of their duties. Reporting mechanisms are robust, featuring progress reports and accountability measures such as APBDes implementation reporting